The impact of excision of benign nonendometriotic ovarian cysts on ovarian reserve: a systematic review - Mohamed, Ahmed A.; Al-Hussaini, Tarek K.; Fathalla, Mohamed M.; El Shamy, Tarek T.; Abdelaal, Ibrahim I.; Amer, Saad A. (Elsevier, 2016)
Background